(untitled) (Journal of Parents and Teachers, 1996)
Fun has become a social necessity, but it is often imposed and not freely chosen. Many young people seek quick pleasures, which can lead to dissatisfaction and dependency. It is crucial to encourage enriching activities that promote well-being and social connection.